THE EFFECT OF SERVANT LEADERSHIP, WORKLOAD AND ORGANIZATIONAL CULTURE ON EMPLOYEES' ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT THE SECRETARIAT OF THE DPRD OF TANAH BUMBU REGENCY - Prapti Nurani; Abdul Kadir (Jurnal Ekonomi, 2023)
This study aims to examine and analyze the influence of Servant Leadership, Workload and Organizational Culture on the Organizational Citizenship Behavior of Employees at the DPRD Secretariat of Tanah Bumbu Regency . This study uses quantitative data analysis methods, namely grouping data based on variables and types of respondents, tabulating data based on variables from all respondents, presenting data for each variable studied, performing calculations to answer the problem formulation, and performing calculations to test the hypothesis that has been proposed. For research that does not formulate a hypothesis, the last step is not carried out . The results of the study show that servant leadership partially has a significant effect on the Organizational Citizenship Behavior variable. Thus it can be concluded that increasing Servant Leadership also increases Organizational Citizenship Behavior. This implies that the better the implementation of servant leadership in the organization by the leadership, the better the tendency for the implementation of Organizational Citizenship Behavior by employees. Workload partially has a significant effect on Organizational Citizenship Behavior variables. There is a significant influence of the workload variable due to the target that must be achieved in terms of how much work an employee must complete